Proceedings of the 2010 ACM Conference on Computer Supported Cooperative Work 2010
DOI: 10.1145/1718918.1718932
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of critical mass and online community survival

Abstract: There is general consensus that critical mass at inception ensures the sustained success of online communities. However, no clear understanding of what constitutes such a 'critical mass' exists and too few quantitative studies have been conducted into the relationship between initial online community interaction and its longer term success to draw any conclusions. In this paper we start to address this gap through a large-scale study of the relationship between IRC chat channel survival and initial chat channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 18 publications
1
35
2
Order By: Relevance
“…User population diversity in chat channels at their inception stage was a significant predictor of the likelihood of channels' long term sustainability [24]. Channels with more diverse populations were more likely to survive than those with more homogeneous populations.…”
Section: Diversity In Online Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…User population diversity in chat channels at their inception stage was a significant predictor of the likelihood of channels' long term sustainability [24]. Channels with more diverse populations were more likely to survive than those with more homogeneous populations.…”
Section: Diversity In Online Communitiesmentioning
confidence: 99%
“…Even with a potentially global reach, online discussion communities often fail to maintain a critical mass of activity [13,24]. Given the much smaller population of potential participants, building sustainable online spaces for local communities is even more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of online participation, studies have shown that "perceived critical mass"-a user's subjective belief that there is a large number of other users who participate in a community or adopt a new technology-has a positive effect on the user's own participation behavior (Markus, 1987;Raban, Moldovan, & Jones, 2010;Van Slyke, IIie, Lou, & Stafford, 2007). Our second study builds on this prior work and extends it to explore whether some people are more sensitive to perceived critical mass than others.…”
Section: Related Studiesmentioning
confidence: 99%
“…[25] gave a definition on the lifetime of IRC channels based on their level of activity. In our experiment, we include user comment frequency into the definition of user lifetime.…”
Section: A Experiments Design 1) Dependent Variablementioning
confidence: 99%